The types of Encyrtidae (Hymenoptera: Chalcidoidea) housed at the Museo de La Plata, Argentina - Loiácono, Marta Susana (2001)
The 608 types of Encyrtidae (Chalcidoidea) housed at the Museo de La Plata (Departamento Cientifico de Entomologia were examined and listed. These types belong to 100 species and 3 subspecies of Encyrtinae. They were described by the following authors: De Santis (71), Annecke (6), Noyes (5), Blanchard (4), Erdoes (3), Annecke & Mynhardt (3), Bennet (1), Brethes (1), De Santis & Fernandes (1), De Santis & Vidal (1), Compere (1), Fidalgo (1), Gahan (1), Ghesquiere (1), Hoffer (1), Kerrich (1) and Mercet (1). For each taxon complete information is given about the original publication, collection data, and its current state of preservation. On the other hand 15 types were placed in a separate list because of their doubtful status.